2021
DOI: 10.1096/fasebj.2021.35.s1.02783
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Genome Editing of the Human Topoisomerase IIα Intron‐19 5′ Splice Site Circumvents Etoposide Resistance in Human Leukemia K562 Cells

Abstract: An essential function of DNA topoisomerase IIα (170 kDa, TOP2α/170) is to resolve DNA topologic entanglements during chromosome dysjunction by introducing transient DNA double‐strand breaks (DSBs). TOP2α/170 is an important target for DNA damage‐stabilizing anticancer drugs, whose clinical efficacy is compromised by drug resistance often associated with decreased TOP2α/170 expression. We recently demonstrated that an etoposide‐resistant K562 clonal subline, K/VP.5, with reduced levels of TOP2α/170, expresses h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a recent interesting study of etoposide-resistant leukemia cells, the CRISPR/Cas9 system was designed to target the exon 19/intron 19 5′ splice site and induce mutations as GAG//GTAA AC → GAG// GTAA GT. The results of this study showed that this gene editing significantly reduced the expression of TOP2α/90 and increased the expression of TOP2α/170, which led to increased sensitivity to etoposide [125]. In addition, studies on chronic myeloid leukemia cells have shown that targeting and disrupting the well-known BCR/ABL oncogene is also possible using CRISPR/Cas9 gene editing and can lead to attenuated proliferation and enhanced apoptosis in imatinib-resistant leukemia cells [126].…”
Section: Crispr/cas9 Gene Editing Applications In Overcoming Drug Res...mentioning
confidence: 80%
See 1 more Smart Citation
“…In a recent interesting study of etoposide-resistant leukemia cells, the CRISPR/Cas9 system was designed to target the exon 19/intron 19 5′ splice site and induce mutations as GAG//GTAA AC → GAG// GTAA GT. The results of this study showed that this gene editing significantly reduced the expression of TOP2α/90 and increased the expression of TOP2α/170, which led to increased sensitivity to etoposide [125]. In addition, studies on chronic myeloid leukemia cells have shown that targeting and disrupting the well-known BCR/ABL oncogene is also possible using CRISPR/Cas9 gene editing and can lead to attenuated proliferation and enhanced apoptosis in imatinib-resistant leukemia cells [126].…”
Section: Crispr/cas9 Gene Editing Applications In Overcoming Drug Res...mentioning
confidence: 80%
“…Studies have shown that in etoposide-resistant leukemia cells there are two isoforms of this enzyme, TOP2α/170 and TOP2α/90, which appear to be the product of alternative RNA processing. TOP2α/170 is the target of anticancer drugs, but it appears that the expression of this isoform decreases in etoposide-resistant leukemia cells, while the expression of TOP2α/90 increases significantly [124,125]. This increased expression may play an important role in drug resistance.…”
Section: Crispr/cas9 Gene Editing Applications In Overcoming Drug Res...mentioning
confidence: 99%